Multifunctional Cellulose and Cellulose-Based (Nano) Composite Adsorbents - Shi, Ru-Jie; Wang, Tian; Lang, Jia-Qi; Zhou, Nong; Ma, Ming-Guo (Frontiers in Bioengineering and Biotechnology, 2022)
In recent years, faced with the improvement of environmental quality problems, cellulose and cellulose-based (nano) composites have attracted great attention as adsorbents. In this review article, we first report the recent progress of modification and functionalization of cellulose adsorbents. In addition, the adsorbents produced by the modification and functionalization of carboxymehyl cellulose are also introduced. Moreover, the cellulose-based (nano) composites as adsorbents are reviewed in detail. Finally, the development prospect of cellulose and cellulose-based (nano) composites is studied in the field of the environment. In this review article, a critical comment is given based on our knowledge. It is believed that these biomass adsorbents will play an increasingly important role in the field of the environment.